Does terrorism work? - Diego Muro (Revista CIDOB d'Afers Internacionals, 2016)
The question of terrorism’s effectiveness is of great political importance to its perpetrators, victims and society in general. Assessing the effectiveness of political violence requires a detailed analysis of the terrorist groups’ whole range of goals and to distinguish between the tactical and strategic levels. Though most clandestine groups fail to achieve their long-term objectives, they do have some success along the way. Terrorism’s capacity to produce the desired effects also depends on other variables and contextual parameters. The tactical and strategic success of a campaign of violence depends on: 1) the capabilities and strength of the perpetrators; 2) the type of end goals; and 3) the capacity and resilience of the society targeted. This article presents the academic debate on terrorism’s effectiveness, analyses the methodological obstacles and provides a guide to the arguments in this special issue.